2012
DOI: 10.1007/s12262-012-0592-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally Detected Gallbladder Cancer- The Controversies and Algorithmic Approach to Management

Abstract: Incidentally discovered gallbladder cancer (IGBC) is defined as the gallbladder cancer (GBC) diagnosed during or after the cholecystectomy done for unsuspected benign gallbladder disease. Laparoscopic cholecystectomy (LC) is the most common procedure performed for benign gallbladder disease worldwide. Majority of GBC patients have associated gallstones. With the advent of ultrasonography more patients are being diagnosed with gallstones and are being subjected to cholecytectomy. IGBC is found in 0.2-2.9 % of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
(45 reference statements)
1
30
1
Order By: Relevance
“…Northern India and Pakistan, East Asia, South America, and Eastern Europe are found to have the highest rates of GBC (1). Incidental GBC is found in 0.2%-2.9% of all cholecystectomies performed for gallstone disease (4,5). Patients with incidental GBC diagnosed with stages Tis and T1a can be treated by simple cholecystectomy alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern India and Pakistan, East Asia, South America, and Eastern Europe are found to have the highest rates of GBC (1). Incidental GBC is found in 0.2%-2.9% of all cholecystectomies performed for gallstone disease (4,5). Patients with incidental GBC diagnosed with stages Tis and T1a can be treated by simple cholecystectomy alone.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with incidental GBC diagnosed with stages Tis and T1a can be treated by simple cholecystectomy alone. Patients with stage T1b and beyond should undergo further surgical treatment (2,5). However, several recent studies have questioned the necessity for routine HPE of all gallbladder specimens.…”
Section: Introductionmentioning
confidence: 99%
“…For pT2 tumors, the 5-year survival rate improves from 20% to 70% if simple cholecystectomy is followed by radical cholecystectomy after the diagnosis of IGBC. 3 Results of this study showed 12 out of 14 cases of IGBC in pT2 stage and 2 case in pT1 stage. Therefore, histopathology should be done for all surgically resected gallbladders, as it is the only tool, which can detect IGBC accurately which improves patient's survival as compared to GBC.…”
Section: Table 2 Incidence Of Igbc In Different Studiesmentioning
confidence: 63%
“…It is also known as occult/inapparent/missed Gallbladder carcinomas. 3 Most of these patients do not have a radiological or intraoperative suspicion for malignancy.…”
mentioning
confidence: 99%
“…Number of patients have GBC incidentally detected at the time of cholecystectomy for gallstone disease, or at the time of histopathological examination of the gallbladder specimen [4]. Similarly, despite looking operable on conventional imaging, many patients of GBC have metastatic disease on laparotomy/diagnostic laparoscopy.…”
mentioning
confidence: 99%